1998
DOI: 10.1080/0260137980170504
|View full text |Cite
|
Sign up to set email alerts
|

In search of a future: adult education and the psychology of the soul

Abstract: This paper takes as its starting point the acceptance of Lauzon's (1998) premise that we are currently engaged in a worldwide shift in meaning-making. The world is no longer served by the dominant means of making meaning --rational-logic. In fact, only the interests of a few are served by rational-logic. This, it is argued, is being replaced by vision-logic and vision-logic is associated with a deepening spirituality. This means that if adult education is to serve a new way of making meaning in the world -visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It has become almost cliché to talk of "changing times." Yet, as I noted earlier, I believe we are engaged in a fundamental shift in human consciousness, which is expressed in how we make sense of the world (epistemology), how we organize socially, and what it means to be human, including the emergence of a new understanding of spirituality (Lauzon, 1998a;1998b). In an earlier work, inspired by the work of Gregory Bateson (1979) (Lauzon, 1995).…”
Section: Spirituality As An Emergent Property Of Human Consciousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become almost cliché to talk of "changing times." Yet, as I noted earlier, I believe we are engaged in a fundamental shift in human consciousness, which is expressed in how we make sense of the world (epistemology), how we organize socially, and what it means to be human, including the emergence of a new understanding of spirituality (Lauzon, 1998a;1998b). In an earlier work, inspired by the work of Gregory Bateson (1979) (Lauzon, 1995).…”
Section: Spirituality As An Emergent Property Of Human Consciousnessmentioning
confidence: 99%
“…As we embrace a spirited adult education, we need to learn to find comfort, or at least some comfort, in complexity, ambiguity, and paradox (Lauzon, 1998b). We need to recognize that the rational mind seeks to resolve ambiguity and paradox, although what is called for sometimes is simply to dwell within it.…”
Section: Canadian Journal Of University Continuing Educationmentioning
confidence: 99%
“…Not all my students could be described as ‘self‐directed’ learners, but all of them enter post‐compulsory education out of choice, investing money and time, and typically with a career in mind. Commenting on the commodification of adult education, Lauzon (1998) has suggested that ‘education for the marketplace’ is based on ‘a psychology of the empty‐self , a self that only finds fulfillment through consumption’ (p. 318; italics in the original). He makes a passionate case for a psychology of the soul, which is ‘about healing and becoming whole again ... a way of knowing ... of understanding and constructing meaning in the world ... of acting in the world’ (ibid., p. 319).…”
Section: The Power Of Imagesmentioning
confidence: 99%
“…Implicit within an education that creates spaces for our spiritual existence is the necessity of grounding it in an ethic of care. First, an ethic of care requires that we ensure that learners in our classroom know they have choice (Lauzon, 1998). Second, we must ensure that we make ourselves available to learners.…”
Section: Fostering An Ethic Of Carementioning
confidence: 99%